2021
DOI: 10.1590/1516-4446-2020-0965
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish cognitive tempo is associated with autistic traits and anxiety disorder symptoms in children with attention-deficit/hyperactivity disorder

Abstract: Objective: To investigate the association of sluggish cognitive tempo (SCT) with autistic traits (ATs) and anxiety disorder symptoms among children with attention-deficit/hyperactivity disorder (ADHD). Methods: A total of 195 children with a DSM-5 diagnosis of ADHD were included. The Barkley Sluggish Cognitive Tempo Scale (BSCTS) was used to measure SCT symptoms. Other study measures included the Autism Spectrum Quotient (AQ), Screen for Child Anxiety and Related Disorders (SCARED), Turgay DSM-IV Disruptive Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Previous studies examining the relationships between SCT and internalizing symptoms and academic impairment have used parent (Camprodon-Rosanas et al, 2017; Ekinci et al, 2021; Jacobson et al, 2018; Lee et al, 2017), teacher (Becker et al, 2021; Bernad et al, 2014, 2016; Vu et al, 2019, and self-reports (Frederick et al, 2019, 2020) of SCT, or a combination of evaluators (Burns et al, 2017; Servera et al, 2018; Smith & Langberg, 2017). There is some evidence that teacher-reported SCT may be more consistently linked to psychopathology dimensions than parent-reported SCT (Becker, 2021), or that teachers may be more equipped to distinguish SCT from ADHD (Burns et al, 2017; Servera et al, 2018; Tamm et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining the relationships between SCT and internalizing symptoms and academic impairment have used parent (Camprodon-Rosanas et al, 2017; Ekinci et al, 2021; Jacobson et al, 2018; Lee et al, 2017), teacher (Becker et al, 2021; Bernad et al, 2014, 2016; Vu et al, 2019, and self-reports (Frederick et al, 2019, 2020) of SCT, or a combination of evaluators (Burns et al, 2017; Servera et al, 2018; Smith & Langberg, 2017). There is some evidence that teacher-reported SCT may be more consistently linked to psychopathology dimensions than parent-reported SCT (Becker, 2021), or that teachers may be more equipped to distinguish SCT from ADHD (Burns et al, 2017; Servera et al, 2018; Tamm et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In populations with ADHD, those with SCT symptoms had higher anxiety scores and autistic traits (Ekinci et al, 2021) and SCT was shown to predict both academic impairment and internalizing psychopathology (Smith & Langberg, 2017). In a study by Servera et al (2018), 2,142 school children were divided into four groups: SCT only, ADHD only, SCT and ADHD combined, and controls.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the other studies using the same diagnostic procedure (Camprodon-Rosanas et al, 2017; Unsel-Bolat et al, 2019). Other studies using the Barkley Sluggish Cognitive Tempo Scale (BSCTS) would identify around 30%–60% of the ADHD patients as having high SCT (Barkley, 2013; Ekinci et al, 2021). The BSCTS contains 14 items reflecting SCT, some not present in the CBCL subscale.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study showed that SCT symptoms were present in about one-third of the ADHD participants (Burns & Becker, 2021). Those individuals with ADHD and SCT have higher levels of emotional and social problems and less externalizing behavior (Carlson & Mann, 2002;Ekinci et al, 2021). The presence of SCT in patients with ADHD often leads to more impaired social functioning (Ferretti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A more parsimonious hypothesis is the transdiagnostic implication of SCT. For example, Ekinci et al [2] verified that higher symptoms of SCT were associated with autism spectrum disorder (ASD) and multiple anxiety disorders in children with ADHD. Brewe et al [3] investigated the incidence of SCT in a small sample comprised of young adults with ASD.…”
Section: Introductionmentioning
confidence: 99%